TRAINING SESSIONS IN THE HIGHER MEDICAL EDUCAT - D. V. Sadchikov (Вестник анестезиологии и реаниматологии, 2018)
When discussing the issue of learning the subject matter of training many researchers still easily replace the following notions and equate their meaning: simulation training, simulation training session and simulation clinic. And they insist that it is easy to develop cognitive skills in doctoring putting special emphasis on manual skills. No simulator or simulation technology can construct the real life situation including relations between the trainer and trainee. Training is an integrated complex of perceptions, thinking and effects. And it is the shift from reality during training that promotes incorporation of doubtful research information into education. Simplification of the problems with priorities given to marginal elements of training results in ineffective decisions especially when high quality treatment is required and medical training sessions cannot solve the problem of lacking medical personnel to provide high-tech medical care.